Penyuluhan Hukum: Perlindungan Data Pribadi sebagai Hak Konsumen dalam Transaksi Online: Perspektif Undang-Undang Nomor 27 Tahun 2022 melalui Radio Maria Indonesia - Joy Zaman Felix Saragih; Rolib Sitorus; Banke, Ricky (Yayasan Literasi Sains Indonesia, 2025)
Legal counseling is an effective method for enhancing legal understanding and awareness among the public. One strategic means of reaching a broader audience is through mass media, particularly radio. The legal counseling activity concerning Personal Data Protection as a Consumer Right in Online Transactions from the perspective of Law Number 27 of 2022, conducted through Radio Maria Indonesia, constitutes a part of the community service program carried out by lecturers of the Law Study Program at Universitas Pelita Harapan (UPH) Medan Campus. The objective of this activity is to provide a more comprehensive understanding to the public regarding the definition, forms, and impact of alleged discrimination in law enforcement, while also explaining preventive measures. Through a communicative approach and the use of simple language, as well as the application of real-life case examples occurring in society, this program is expected to foster shared awareness and encourage active public participation in supporting fair and firm law enforcement. This study evaluates the extent to which legal counseling through radio is effective in shaping a critical attitude and more responsive behavior among the public towards Personal Data Protection as a Consumer Right in online transactions. The findings indicate that radio proves to be an effective medium for legal education, particularly in areas with limited access to formal education or digital technology.